Preparação e caracterização de amido de milho modificado com óleo de coco (Cocos nucifera L) - Pereira, Mayra Cristina Silva (2016)
Starch is a biopolymer obtained from renewable sources, made up of two major macromolecules: amylopectin and amylose, it is used for various purposes. Biopolymers are alternatives to synthetic polymers, for having a short life cycle compared to them, placing environmental and socioeconomic factors as major concerns by the scarcity and harmful impacts of oil extraction processes and also the availability and low cost of acquisition of such material. Corn starch was modified by transesterification process with coconut oil to obtain unique multifunctional characteristics and versatility in applications, conferring hydrophobic characteristics to the polymer for improved moisture retention when intended for use in biodegradable packaging. characterization of modified starch was carried out and control, as well as the binary blends of both starches obtained in junction with polyvinyl alcohol (PVA), for more comprehensive comparison. The analyzes used to characterize the starches were thermal analysis (TG-DSC) and spectroscopy in the infrared (FT-IR), the blends were were also characterized by TG-DSC and FT-IR, in addition to being given the Swelling Index the water Transmission to Steam and wetness angle. The elucidation of the chemical structure obtained by transesterification of corn starch and consequent comparison with the control maize starch was done by nuclear magnetic resonance, X-ray diffraction and Scanning Electron Microscopy. As a result, the blends formed from this showed low permeation rates to water and water vapor relative to other biodegradable films, in addition to uniformity, low thickness and high hydrophobicity compared to other biodegradable films already produced, enabling viability as a biodegradable packaging.